Pengaruh Fasilitas Belajar dan Motivasi Belajar terhadap Kedisiplinan Belajar Siswa - Murniatin; Abdullah Hadziq (Program Pascasarjana UNU Surakarta, 2022)
Discipline in the educational process is indispensable because it is not only to maintain the conditions of the learning and teaching atmosphere smoothly but also to create a strong personality for each student. Many factors can influence the formation of student learning disciplines, such as learning facilities in schools and student learning motivation. The study aims to partially and partially determine the influence of learning facilities and motivation on the learning discipline of class VIII MTs Negeri 7 Sragen students for the 2020/2021 academic year partially and simultaneously. Research is field research with a quantitative approach. The study population was all students of class VIII MTs Negeri 7 Sragen, as many as 131 students, a sample of 35 students was taken by simple random sampling. The data collection technique uses questionnaires that have been tested for validity and reliability. The data analysis technique uses multiple linear regression analysis previously performed classical assumption analysis. The results of the study found: (1) There is a significant favorable influence of learning facilities on student learning discipline, so it can be interpreted that the more complete and well-managed learning facilities, the more it improves student discipline in learning, (2) Ada significant positive influence of learning motivation on student learning discipline, so it can be interpreted that the higher the student's motivation in learning, the more it improves student learning discipline and (3) There is an influence of learning facilities and learning motivation on student learning discipline, so it can be interpreted that the more complete and well-managed learning facilities are supported by the higher the motivation to learn, the more it increases student discipline in learning. From these results, it can be suggested that teachers cooperate with all stakeholders to participate in helping students to realize the need for discipline in learning. It is hoped that teachers can carry out creative and exciting learning so students can be motivated to learn. The creation of classrooms that are conducive and comfortable for learning helps to increase students' motivation and discipline in knowledge. The school, in collaboration with the Education Office, completes student learning facilities so that the learning process can take place conductively, which can increase student motivation in learning and support student learning discipline so that student learning achievement can be achieved optimally.